The The Obstetric Panorama in the Metropolitan Region of Baixada Santista – Brazil: Prevalence and Profile of Parturients - Eliana Souza dos Santos dos Santos; Petterson Yuri Andrade dos Santos; Lígia Maria Gonçalves Rodrigues Xavier; Elaine Marcilio Santos; Gustavo Duarte Mendes; Juliana Maria Altavista Sagretti Gallo; Sandra Kalil Bussadori; Carolina Mayumi Iegami; Marcela Leticia Leal Gonçalves; Edgar Maquigussa; Ana Paula Sobral (Epidemiology, Biostatistics and Public Health)
Background: The birth of a child is a significant milestone for mothers and families. However, concerns regarding the type and safety of delivery persist. Evidence shows that vaginal delivery provides immunological and respiratory benefits for the baby and offers protective factors for the mother. Despite this, cesarean sections remain prevalent, particularly in developing regions.